Azido and Tetrazolo 1, 2, 4, 5‐Tetrazine N‐Oxides. Issue 13 (23rd February 2017) - Chavez, David E.; Parrish, Damon A.; Mitchell, Lauren; Imler, Greg H.
Abstract: This study presents the synthesis and characterization of the oxidation products of 3, 6‐diazido‐1, 2, 4, 5‐tetrazine (1 ) and 6‐amino‐[1, 5‐ b ]tetrazolo‐1, 2, 4, 5‐tetrazine (2 ). 3, 6‐Diazido‐1, 2, 4, 5‐tetrazine‐1, 4‐dioxide was produced from oxidation with peroxytrifluoroacetic acid, and more effectively using hypofluorous acid, and 2 can be oxidized to two different products, 6‐amino‐[1, 5‐b]tetrazolo‐1, 2, 4, 5‐tetrazine mono‐N‐oxide and di‐N‐oxide. These N‐oxide compounds display promising performance properties as energetic materials. Abstract : The oxidation products of 3, 6‐diazido‐1, 2, 4, 5‐tetrazine (1 ) and 6‐amino‐[1, 5‐ b ]tetrazolo‐1, 2, 4, 5‐tetrazine (2 ) have been characterized. 3, 6‐Diazido‐1, 2, 4, 5‐tetrazine‐1, 4‐dioxide (see picture) was produced by oxidation of 1 with peroxytrifluoroacetic acid, and more effectively using hypofluorous acid, and 2 can be oxidized to its mono‐ and di‐N‐oxide. These products display promising performance as energetic materials.